Unveiling the Mysteries of Gut CrAssphages: A Step Forward in Understanding the Human Virobiome - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
A recent study published in the journal Nature and as preprint has revealed a new structural atlas of gut crAssphages, a type of virus that is commonly found in the human gut microbiome.1,2 T his ground breaking research sheds light on the structure and function of these viruses, which play a crucial role in the ecology of the human gut microbiome. The human gut microbiome is a complex and diverse ecosystem of microorganisms that play an important role in human health and disease. Viruses, including crAssphages, are an integral part of this ecosystem, but their structure and function have remained poorly understood until now.